Validation of mortality risk scores after esophagectomy - Sabine Schiefer; Nerma Crnovrsanin; Ingmar F. Rompen; Nicolas Jorek; Mohammed Al-Saeedi; Thomas Schmidt; Henrik Nienhüser; Leila Sisic (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Oncological esophagectomy is the mainstay in esophageal cancer treatment, but perioperative mortality remains a significant concern. Various scoring systems exist to identify patients at high risk for postoperative complications and death. In the following, we aim to evaluate and compare these different scoring systems. Methods We analyzed data from 714 patients who underwent esophagectomy between 2002 and 2021. Each patient’s risk was calculated using three models: the International Esodata Study Group (IESG) 90-day mortality risk prediction, the Steyerberg 30-day mortality score, and the Fuchs et al. preoperative in-hospital mortality score (Fuchs score). The diagnostic performance of these models was assessed using the area under the receiver operating characteristic (ROC) curves. Results Of the 714 patients, the majority (87.67%) underwent abdomino-thoracic esophagectomy with intrathoracic anastomosis. The IESG score classified 52.1% as very low, 26.6% low, 17.5% middle, 2.8% high, and 1% as very high risk, while the Fuchs score identified 94.5% as low-risk and 5.5% as high-risk patients. Mortality rates were 6.9% at 90 days, 3.4% at 30 days, and 6.7% in-hospital. The area under the ROC curve was 0.634 (95%CI: 0.557–0.712) for the IESG model, 0.637 (95%CI: 0.526–0.747) for the Steyerberg score, and 0.686 (95%CI: 0.611–0.760) for the Fuchs score. Conclusions Existing risk score systems provide a possibility for preoperative risk stratification, particularly for identifying high-risk patients. However, due to their limited predictive ability, improvements are needed to apply these strategies effectively in clinical practice.